Complications of measles: a case series - Xerri, Thelma (BMJ Case Rep, 2020)
Measles, which was once thought to be a disappearing viral infection due to effective vaccination, has been re-emerging globally, with increasing cases in adolescents and adults. This has been attributed to anti-vaccination campaigning in the early 21st century, which has resulted in a drop in overall herd immunity. In this case series we report three patients with complications secondary to measles who presented to a hospital in Malta in 2019. Through this series, we discuss the range of possible complications caused by the measles virus, ranging from mild viraemic symptoms to multiorgan involvement which could possibly lead to high-dependency care and may even be fatal. We also highlight recent global statistics which reflect the exponential increase in the incidence of measles, with a special focus on Europe. It is emphasised that vaccine education and compliance with the two-dose measles vaccine should be implemented worldwide.